Paper-based devices for rapid diagnostics and testing sewage for early warning of COVID-19 outbreak - Hui, Qingxin; Pan, Yuwei; Yang, Zhugen (Elsevier, 2020)
oronavirus disease (COVID-19), caused by SARS-CoV-2, evolved into a global pandemic in 2020, and the outbreak has taken an enormous toll on individuals, families, communities and societies around the world. One practical and effective strategy is to implement rapid case identification based on a rapid testing to respond to this public health crisis. Currently, the available technologies used for rapid diagnostics include RT-PCR, RT-LAMP, ELISA and NGS. Still, due to their different limitations, they are not well suited for rapid diagnosis in a variety of locations. Paper-based devices are alternative approaches to achieve rapid diagnosis, which are cost-effective, highly selective, sensitive, portable, and easy-to-use. In addition to individual virus screening, wastewater-based epidemiology has been emerged to be an effective way for early warning of outbreak within the population, which tests viral genome sequence to reflect information on the spread and distribution of the virus because SARS-CoV-2 can be shed into wastewater through the feces and urine from infected population. In this paper, we describe paper-based device as a low-cost and rapid sensor for both diagnosis and testing of sewage for early warning of outbreak. More importantly, the device has great potential for real-time detection in the field, without any advanced facilities or well-trained and skilled personnel, and provides early warning or timely intervention of an outbreak of pandemic.
Keywords: Paper-based devices; Rapid diagnosis; Wastewater-based epidemiology; COVID-19; Early warning system